The current trends of bioethanol production from cheese whey using yeasts: biological and economical perspectives - Tesfaw, Asmamaw (Frontiers in Energy Research, 2023)
Besides organic compounds such as lactose and proteins, cheese whey is rich in other nutrients. Damping of these valuable compounds to the environment, first, harms the environment, and second, it wastes valuable resources. Therefore, this review aims to find out the current progress on the valorization of cheese whey for ethanol production. Efficient ethanol-producing yeasts like Saccharomyces cerevisiae have no pathway to utilize lactose and, therefore, they can be co-cultured with microbes that can produce β-galactosidase. In addition, chemical, biological, and physical hydrolysis of lactose can be used to produce ethanol from cheese whey. Ethanol production from unsterilized or unpasteurized whey is very promising and this reduces the production cost significantly. This suggests that the ethanol-producing yeasts are competent against the lactic acid bacteria that are commonly found in cheese whey. Despite the presence of central metabolic genes associated with ethanol production from different sugars in some yeasts, these yeasts can’t ferment the different sugars and this is basically due to a lack of the different sugar transport systems in the yeasts. Therefore, additions of different sugars to whey to increase the sugar content for economical ethanol production are impaired by catabolite repressions. However, catabolite repression can be significantly reduced by metabolic engineering by targeting sugar transporter proteins like the major facilitator superfamily (MFS), particularly LAC, CEL2, HGT, RAG, and KHT. Therefore, this enhances ethanol production from cheese whey supplemented with a variety of sugars. Currently, nanoparticles and metal-organic frameworks coated immobilization of S. cerevisiae produced higher ethanol from lignocellulosic substrates than the classical carries such as alginates; however, studies of such immobilizing materials on Kluveromyces spp for ethanol production are very limited, and open for research. Electro-fermentation, an emerging bioprocess to control microbial fermentative metabolism, boosts ethanol production, enables the production of 14 % (v/v) ethanol, and shortens the fermentation time of high sugar-containing whey. Generally, utilizing efficient yeast (possibly by adaptive evolution and genetic engineering) at optimal fermenting conditions enabled to production of economical ethanol from cheese whey that contains higher sugars (greater than 15%) at the large-scale cheese processing industries.